About sound science, stable isotope dilution, blasphemy and heresy. (August 2013) - Svensson, Leif D
The molar ratio between an analyte and its equal labeled with stable isotope(s), used as a bioanalytical IS, is here suggested as an essential (and currently not commonly applied) validation parameter. This parameter, when calculated and measured, gives the possibility for the bioanalyst to compare calibration graphs and QC samples over time independently of added amount of IS. Additionally, when QC samples and calibration samples do not agree it is obvious to identify where the discrepancies are. Whether calibration samples are needed when this parameter is extensively and carefully validated and understood, is also discussed.